Policy Evaluation Of Minimum Service Standards For Hypertension Health Services At Mabelopura Health Center - Halida, Halida; Mufti, Mohammad Irfan; Asrifai, Asrifai (PT. Anagata Sembagi Education, 2024)
Hypertension is a chronic medical condition in which arterial blood pressure increases, causing the heart to work harder. At Puskesmas Mabelopura, hypertension has not yet reached the Minimum Service Standard (MSS) target with an achievement of only 68.61% of the 95% target. This study evaluated the SPM policy on hypertension services at the Mabelopura Health Center using a descriptive qualitative method with informants from Key Informants and Triangulated Informants. The results showed that the implementation of SPM Hypertension only reached 68.61% of the 95% target, indicating that the target has not been achieved. Health services are in accordance with SPM standards but not optimal, due to differences in central target data with Puskesmas data and limited human resources. The low number of community visits for hypertension screening, due to the community's lack of perceived importance of routine control, was also a major factor. This study concluded that to achieve SPM targets, intensive efforts are needed from Puskesmas Mabelopura and the Health Office of Palu City to establish better communication with Pusdasten and increase community awareness of the importance of routine check-ups. Thus, it is expected that Puskesmas Mabelopura can be more effective in achieving SPM targets and improving the quality of life of people with hypertension in the area.